A Continuous Robust Attitude Control Approach for Quadrotors Subject to Disturbance - Hua, Hean; Fang, Yongchun; Zhang, Xuetao; Qian, Chen (2019 IEEE International Conference on Robotics and Biomimetics (ROBIO), 2019)
In this paper, a continuous robust attitude control approach is proposed, which can achieve exponential stability even in the presence of external disturbance. In particular, on the basis of configuration space SO(3), the augmented dynamics of the system are transformed into a quasi-chained form. Subsequently, a continuous sliding mode approach is put forward, which is composed of a sliding mode differentiator and a sliding mode controller. Different from most reported approaches, the proposed control law is essentially continuous and the equilibrium point is exponentially stable even in the presence of complex unknowns. Finally, the simulation result illustrates the high tracking accuracy and strong robustness of the proposed method.